ASSESMENT OF THE EFFECTS OF HOUSE COUNTRY MACROECONOMICS ON PERFORMANCE CROSS LISTED FIRMS IN EAST AFRICA - Pastory, Dickson (J-MACC : journal of management and accounting, 2022)
This study makes assessment of the effects of host country macroeconomic factors on the performance of cross listed firms in East Africa. It uses quarterly time series from March 2010 to December 2020. The study used stock prices of five Kenyan companies that are cross listed in the stock markets of Uganda and Tanzania. The overall model capturing the impact of the macroeconomic factors on the average prices of stocks shows that interest rate exerts positive and significant impact on the stock market performance, while, inflation has negative and significant effects on the stock market performance in both Uganda and Tanzania. GDP is statistically not significant in influencing the stock prices in both countries. On the other hand, the model that captures individual effect provides mixed result in both Uganda and Tanzania, with the negative effect of inflation reported in three firms in Uganda and two firms in Tanzania; while, a positive effect is found in one firm listed in Uganda and two firms listed in Tanzania. Similarly, the effect of interest rate is positive for three firms in both Uganda and Tanzania; and it is negative in one firm listed in both USE and DSE. GDP negatively affect stock prices of two firms in Tanzania and positively affect the prices of one firm in Uganda.